A kind of highly water-absorbent konjac hydrogel polymer and preparation method thereof

Through acetylation modification and metal ion crosslinking, the stability and mechanical strength of the konjac hydrogel are enhanced, and porous structures are generated through nanocellulose and interface induction method, which solves the problem of poor stability of the konjac hydrogel under different environmental conditions, and achieves the effect of high water absorption and slow expansion.

CN119144054BActive Publication Date: 2025-04-29SHANGHAI XUQING MEDICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411630785.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-29
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Konjac hydrogel has poor physical and chemical stability under different environmental conditions, especially in acidic environments, which reduces viscosity, affects its expansion and water absorption ability, and is insufficient mechanical strength, making it difficult to maintain stability in complex digestive systems.

Method used

By acetylation of modified konjac glucomanan, acetylated groups are introduced to reduce hydrophilicity and delay the entry rate of moisture. At the same time, metal ion cross-linking and cetyl modified chitosan are used to enhance the stability and mechanical strength of the gel network, and porous structures are generated through nanocellulose and interface induction methods to improve water absorption performance and structural stability.

Benefits of technology

It significantly improves the stability and mechanical strength of konjac hydrogel, delays the initial water absorption rate, and maintains structural integrity in an acidic environment, enhancing its application effect in the digestive tract.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144054B_ABST
    Figure CN119144054B_ABST
Patent Text Reader

Abstract

This invention belongs to the field of functional polymer technology, specifically relating to a highly absorbent konjac hydrogel polymer and its preparation method. The konjac hydrogel polymer comprises the following raw materials in parts by weight: 30-40 parts acetylated konjac glucomannan, 10-15 parts modified chitosan, 5-8 parts calcium chloride solution, 1-3 parts acetic acid solution, 3-5 parts nanocellulose, 2-5 parts beeswax, 10-15 parts MCT medium-chain triglycerides, and 1-3 parts emulsifier. This invention reduces hydrophilicity by acetylated modified konjac glucomannan, delaying water absorption and improving stability in acidic environments; cross-linking enhances mechanical strength; chitosan modification increases hydrophobicity; and nanocellulose improves mechanical strength and toughness. Surface coating with a mixture of beeswax and MCT modifies surface properties and delays water absorption. An interface-induced method combined with freeze-drying technology generates a porous structure, improving water absorption efficiency and structural integrity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymers, and particularly relates to a highly water-absorbent konjac hydrogel polymer and a preparation method thereof. Background Art

[0002] Konjac hydrogel, a highly absorbent material based on konjac glucomannan (Konjac Glucomannan), has been widely used in various fields, particularly in food, medicine, and health, due to its excellent water absorption and swelling properties. Konjac glucomannan, a natural non-starch polysaccharide, is a type of dietary fiber with a molecular structure composed of glucose and mannose. Upon contact with water, this fiber absorbs large amounts of water and forms a viscous gel-like substance, capable of absorbing water exceeding 50 times its own volume. This property makes Konjac hydrogel an ideal candidate for weight management and gut health products, as it rapidly expands in the gastrointestinal tract, increasing satiety while slowing gastric emptying, helping to reduce food intake. Furthermore, the viscous properties of Konjac glucomannan help promote intestinal motility, improve intestinal function, reduce constipation, and regulate the balance of intestinal flora. However, despite Konjac hydrogel's remarkable swelling and water absorption capabilities, its practical application still faces several technical challenges, particularly its physical and chemical stability under various environmental conditions. The viscosity performance of konjac hydrogel is highly sensitive to external factors such as pH value, ionic strength and temperature of solution. Especially in acidic environment (such as gastric acid), the viscosity of konjac glucomannan tends to significantly decline, and then weakens its expansibility and water absorption capacity, and this viscosity change not only affects the physical stability of konjac hydrogel, but also may reduce its actual effect in vivo. Although konjac hydrogel possesses good expansibility, its mechanical strength is relatively weak. Under the mechanical force of gastrointestinal tract or external pressure, gel structure easily breaks or is out of shape, causes it to be difficult to keep stability in the digestive system environment of complexity, and this limits its application in fields such as food and pharmaceutical preparations. Therefore, based on the problems referred to above, it is extremely necessary to research and develop a kind of konjac hydrogel polymer of high water absorbability, high stability and slow expansion. Summary of the Invention

[0003] In view of the defects of the prior art, the object of the present invention is to provide a highly water-absorbent konjac hydrogel polymer and a preparation method thereof.

[0004] The technical effect of the present invention is achieved through the following technical solution: a highly water-absorbent konjac hydrogel polymer, which comprises the following raw materials in parts by weight: 30-40 parts of acetylated konjac glucomannan, 10-15 parts of modified chitosan, 5-8 parts of calcium chloride solution, 1-3 parts of acetic acid solution, 3-5 parts of nanocellulose, 2-5 parts of beeswax, 10-15 parts of MCT medium-chain triglycerides and 1-3 parts of emulsifier.

[0005] Preferably, the emulsifier is any one of lecithin, Tween-80 and glyceryl monostearate.

[0006] Preferably, the concentration of the calcium chloride solution is 0.2-0.5M.

[0007] Preferably, the concentration of the acetic acid solution is 0.1-0.2M.

[0008] Preferably, the specific preparation steps of the acetylated konjac glucomannan are as follows:

[0009] A1: Konjac glucomannan is added to distilled water and stirred to dissolve uniformly to obtain a 5-10 wt% konjac glucomannan solution; the konjac glucomannan solution is cooled to 0-5°C, and then sodium citrate is added to adjust the pH to 6.5-7. Acetic anhydride is slowly added dropwise with continuous stirring, and the mixture is stirred for 2-3 hours. After the reaction is completed, ethanol 3-4 times the volume of the solution is added to terminate the reaction. The mixture is centrifuged at 6000 rpm for 10 minutes, washed with distilled water until neutral, and dried under vacuum at 50-60°C to constant weight to obtain acetylated konjac glucomannan.

[0010] Preferably, in step A1, the amount of acetic anhydride used is 1-2% of the volume of the konjac glucomannan solution.

[0011] Preferably, the specific preparation steps of the modified chitosan are as follows:

[0012] B1: Dissolve chitosan in 0.1M acetic acid aqueous solution and stir to dissolve uniformly to obtain a chitosan solution with a concentration of 1-2wt%; dissolve cetyltrimethylammonium bromide in dimethyl sulfoxide solvent, heat to 50°C in a water bath, stir to dissolve uniformly to obtain a cetyltrimethylammonium bromide solution;

[0013] B2: The hexadecyltrimethylammonium bromide solution prepared in step B1 was slowly added dropwise to the chitosan solution, heated in a water bath to 50-60°C, the pH was controlled to 4-5, and the reaction was continued for 3-6 hours. The reaction solution was then poured into an ethanol solution 3-4 times the total volume of the solution in three times, centrifuged, filtered, and washed with ethanol three times. The solution was then vacuum dried at 60°C to a constant weight to obtain modified chitosan.

[0014] Preferably, in step B1, the ratio of the amount of hexadecyltrimethylammonium bromide to the amount of dimethyl sulfoxide solvent is 0.15-0.3 g:1 mL;

[0015] Preferably, in step B2, the volume ratio of the cetyltrimethylammonium bromide solution to the chitosan solution is 0.6 to 1:1.

[0016] Preferably, another aspect of the present invention is to provide a method for preparing a highly water-absorbent konjac hydrogel polymer, wherein the specific preparation steps are as follows:

[0017] S1: dissolving acetylated konjac glucomannan in distilled water and stirring to dissolve uniformly to obtain a 1-3 wt% acetylated konjac glucomannan solution; dissolving modified chitosan in acetic acid solution and stirring to dissolve uniformly to obtain a chitosan solution; adding nanocellulose to distilled water and dispersing uniformly by ultrasonic treatment to obtain a 1-2 wt% nanocellulose suspension;

[0018] S2: slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH to 5.5-6.5 during the process, stirring continuously for 30-60 minutes, gradually adding the nanocellulose suspension prepared in step S1, stirring continuously for 30-50 minutes, and gradually adding the calcium chloride solution, stirring continuously for 30-60 minutes to obtain a gel solution;

[0019] S3: Add three-quarters of MCT medium-chain triglycerides to a beaker, add an emulsifier, and stir to dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, set the speed to 2000-3000 rpm, and slowly add the gel solution prepared in step S2 under continuous stirring, and emulsify for 15-30 minutes. After emulsification, let it stand for 30 minutes to obtain an emulsion;

[0020] S4: pre-freezing the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freezing it at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-drying it to obtain gel particles;

[0021] S5: beeswax and one-quarter of the weight of MCT medium-chain triglycerides are mixed and heated in a water bath to 70° C. to completely dissolve to obtain a coating liquid. The gel particles prepared in step S3 are preheated to 40° C. and then added to the coating liquid. After stirring for 1 to 2 minutes, the gel particles are separated by a sieve and immediately cooled to 4° C. to solidify to obtain a konjac hydrogel polymer.

[0022] Preferably, in step S2, the nanocellulose suspension is added in three batches; the calcium chloride solution is added in four batches;

[0023] Preferably, the freeze-drying treatment in step S4 is performed as follows: the freeze dryer temperature is set to -50°C and the vacuum degree is 0.1 mbar, the pre-frozen gel is dried at -50°C for 24 hours, and then the temperature is increased to 20°C at a rate of 1°C / min and dried for 6 hours.

[0024] The beneficial effects of the present invention are as follows:

[0025] The present invention carries out acetylation modification to konjac glucomannan, effectively reduces its hydrophilicity, delays the speed that moisture enters gel, improves the stability of gel under acidic and neutral conditions simultaneously, the introduction of acetylated groups can also produce hydrophobic interaction with the long-chain alkyl of hexadecyl modified chitosan, strengthens stability and the mechanical strength of gel network, in addition, acetylation gives hydrogel certain acid resistance, makes it possible to maintain structural integrity in gastric acid environment, thereby strengthens its application effect in complex digestive system. Multivalent metal ion crosslinking (calcium ion) is by forming stable crosslinking network with konjac glucomannan, further improves the mechanical strength of hydrogel, metal ion crosslinking not only strengthens the structural stability of gel, also can regulate and control the hydrophilicity of gel, delay initial water absorption rate, progressively promote the water absorption performance after water molecules penetrate into crosslinking network simultaneously, show the high water absorbability that progressively accelerates. The dual structure that acetylation modification and metal ion crosslinking jointly construct, not only can slow down initial water absorption rate, also provides sufficient adsorption sites for subsequent water diffusion, makes hydrogel keep good mechanical strength in water absorption process. The hexadecyl long-chain modification of chitosan can form a tighter molecular arrangement in the gel network through hydrophobic interaction, making the gel more stable during water absorption and swelling, and not easy to break or become unstable. The hexadecyl-modified chitosan can also play a synergistic role in the interface induction method. Due to the introduction of hydrophobicity, a more stable phase separation structure is formed at the water-oil interface, promoting the formation of pores.

[0026] The present invention significantly improves the mechanical strength and toughness of the hydrogel by introducing nanocellulose. As a physical reinforcement material, nanocellulose interacts with the cross-linked network of konjac glucomannan to form a stable support structure, making the hydrogel less likely to break or become unstable during the water absorption and swelling process. At the same time, the high specific surface area of ​​nanocellulose helps to enhance the water absorption performance in the later stage. Through its hydrophilicity and nanoscale structure, nanocellulose promotes the diffusion of water inside the gel while improving the structural strength, thereby improving the high water absorption capacity of the hydrogel. A layer of mixed coating liquid of natural edible lipophilic substances beeswax and MCT medium-chain triglycerides is coated on the surface of the hydrogel to further adjust the surface properties of the hydrogel. The coating has a certain hydrophobicity and can delay the entry of water from the outside into the gel, further achieving the effect of slow water absorption. In addition, plant wax has good biocompatibility and safety, and can also protect the structural integrity of the hydrogel in the digestive tract, preventing it from being prematurely degraded and prolonging its residence time in the digestive tract.

[0027] The present invention utilizes an interfacial induction method combined with freeze-drying technology to generate a porous structure inside the hydrogel, significantly improving its specific surface area and water transfer efficiency. The introduction of the porous structure effectively slows down the initial water absorption rate, and based on the need for water, it gradually enters the interior of the gel through these pores, thereby achieving the effect of sustained water absorption. At the same time, freeze-drying technology forms a stable and uniform microporous network, allowing the hydrogel to expand rapidly after absorbing a certain amount of water, increasing its water absorption capacity and maintaining the structural integrity of the gel. Through the above synergistic effect, not only is the residence time of the hydrogel in the digestive tract prolonged, but its applicability in pharmaceutical preparations and dietary supplements is also improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0029] Figure 1 It is a deionized water water absorption test graph of the konjac hydrogel polymer prepared in Example 2 of the present invention and Comparative Examples 1 to 4;

[0030] Figure 2 2 is a graph showing the simulated gastric fluid water absorption test of the konjac hydrogel polymers prepared in Example 2 of the present invention and Comparative Examples 1 to 4;

[0031] Figure 3 2 is a test chart of the simulated intestinal fluid water absorption of the konjac hydrogel polymers prepared in Example 2 of the present invention and Comparative Examples 1 to 4;

[0032] Figure 4 2 is a graph showing the compressive strength test results of the konjac hydrogel polymers prepared in Example 2 of the present invention and Comparative Examples 1 to 4;

[0033] Figure 5 The biocompatibility test of the konjac hydrogel polymer prepared in Examples 1 to 3 of the present invention is as follows;

[0034] Figure 6 It is the SEM scanning pattern of the konjac hydrogel polymer prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention. It should be noted that unless otherwise specified, the raw materials involved in the present invention were purchased through conventional commercial channels.

[0036] Example 1: A highly absorbent konjac hydrogel polymer comprises the following raw materials in parts by weight: 30 parts of acetylated konjac glucomannan, 10 parts of modified chitosan, 5 parts of calcium chloride solution, 1 part of acetic acid solution, 3 parts of nanocellulose, 2 parts of beeswax, 10 parts of MCT medium chain triglycerides and 1 part of emulsifier.

[0037] Preparation of acetylated konjac glucomannan:

[0038] A1: Konjac glucomannan was added to distilled water and stirred to dissolve uniformly to obtain a 5 wt% Konjac glucomannan solution; 200 mL of the Konjac glucomannan solution was cooled to 5°C, and then sodium citrate was added to adjust the pH to 7. 2 mL of acetic anhydride was slowly added dropwise with continuous stirring. The mixture was stirred for 2 h. After the reaction, 600 mL of ethanol was added to terminate the reaction. The mixture was centrifuged at 6000 rpm for 10 min, washed with distilled water until neutral, and dried under vacuum at 50°C to constant weight to obtain acetylated Konjac glucomannan;

[0039] Preparation of modified chitosan:

[0040] B1: Dissolve chitosan in 0.1M acetic acid aqueous solution and stir to dissolve uniformly to obtain a chitosan solution with a concentration of 1wt%. Dissolve 75mg of hexadecyltrimethylammonium bromide in 500mL of dimethyl sulfoxide solvent, heat to 50°C in a water bath, and stir to dissolve uniformly to obtain a hexadecyltrimethylammonium bromide solution.

[0041] B2: Slowly add 500 mL of the hexadecyltrimethylammonium bromide solution prepared in step B1 dropwise to 500 mL of the chitosan solution, heat in a water bath to 50°C, control the pH to 4, react for 6 h, pour the reaction solution into 3000 mL of ethanol solution three times, centrifuge, filter, and wash with ethanol three times, and dry in a vacuum at 60°C to constant weight to obtain modified chitosan;

[0042] Preparation of konjac hydrogel polymer:

[0043] S1: dissolving acetylated konjac glucomannan in distilled water and stirring to dissolve uniformly to obtain a 1 wt% acetylated konjac glucomannan solution; dissolving modified chitosan in 0.1 M acetic acid solution and stirring to dissolve uniformly to obtain a chitosan solution; adding nanocellulose to distilled water and dispersing uniformly by ultrasonic treatment to obtain a 1 wt% nanocellulose suspension;

[0044] S2: Slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH to 5.5 during the process, stirring continuously for 30 minutes, then adding the nanocellulose suspension prepared in step S1 in three batches, stirring continuously for 30 minutes, and adding 0.2M calcium chloride solution in four batches, stirring continuously for 30 minutes to obtain a gel solution;

[0045] S3: Add three-quarters of MCT medium-chain triglycerides and lecithin to a beaker, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, set the speed to 2000 rpm, and slowly add the gel solution prepared in step S2 under continuous stirring, and emulsify for 30 minutes. After emulsification, let it stand for 30 minutes to obtain an emulsion;

[0046] S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel. Set the freeze dryer temperature to -50°C and the vacuum degree to 0.1 mbar. Dry the pre-frozen gel at -50°C for 24 hours, then heat it to 20°C at a rate of 1°C / min and dry it for 6 hours to obtain gel particles.

[0047] S5: Mix beeswax and one-quarter of the weight of MCT medium-chain triglycerides, heat in a water bath to 70°C to completely dissolve them, and obtain a coating liquid. Preheat the gel particles prepared in step S3 to 40°C, and then add them to the coating liquid. After stirring for 1 minute, separate the gel particles with a sieve, and immediately cool to 4°C to solidify to obtain a konjac hydrogel polymer.

[0048] Example 2: A highly absorbent konjac hydrogel polymer comprises the following raw materials in parts by weight: 40 parts of acetylated konjac glucomannan, 15 parts of modified chitosan, 8 parts of calcium chloride solution, 3 parts of acetic acid solution, 5 parts of nanocellulose, 5 parts of beeswax, 15 parts of MCT medium chain triglycerides and 3 parts of emulsifier.

[0049] Preparation of acetylated konjac glucomannan:

[0050] A1: Konjac glucomannan was added to distilled water and stirred to dissolve uniformly to obtain a 10 wt% Konjac glucomannan solution; 200 mL of the Konjac glucomannan solution was cooled to 0°C, and then sodium citrate was added to adjust the pH to 6.5. 4 mL of acetic anhydride was slowly added dropwise with continuous stirring, and the mixture was stirred for 3 h. After the reaction, 800 mL of ethanol was added to terminate the reaction, and the mixture was centrifuged at 6000 rpm for 10 min. The mixture was washed with distilled water until neutral, and dried under vacuum at 60°C to constant weight to obtain acetylated Konjac glucomannan;

[0051] Preparation of modified chitosan:

[0052] B1: Dissolve chitosan in 0.1M acetic acid aqueous solution and stir to dissolve uniformly to obtain a chitosan solution with a concentration of 2wt%. Dissolve 150mg of hexadecyltrimethylammonium bromide in 500mL of dimethyl sulfoxide solvent, heat to 50°C in a water bath, and stir to dissolve uniformly to obtain a hexadecyltrimethylammonium bromide solution.

[0053] B2: 300 mL of the hexadecyltrimethylammonium bromide solution prepared in step B1 was slowly added dropwise to 500 mL of the chitosan solution, heated to 60°C in a water bath, and the pH was controlled to 5. After reacting for 5 h, the reaction solution was poured into 3200 mL of ethanol solution three times, centrifuged, filtered, and washed with ethanol three times. The solution was then vacuum-dried at 60°C to a constant weight to obtain modified chitosan.

[0054] Preparation of konjac hydrogel polymer:

[0055] S1: dissolving acetylated konjac glucomannan in distilled water and stirring to dissolve uniformly to obtain a 3 wt% acetylated konjac glucomannan solution; dissolving modified chitosan in 0.2 M acetic acid solution and stirring to dissolve uniformly to obtain a chitosan solution; adding nanocellulose to distilled water and dispersing uniformly by ultrasonic treatment to obtain a 2 wt% nanocellulose suspension;

[0056] S2: The chitosan solution prepared in step S1 was slowly added to the acetylated konjac glucomannan solution, and the pH was controlled to 6.5 during the process. After stirring for 60 minutes, the nanocellulose suspension prepared in step S1 was added in three batches, and the stirring was continued for 50 minutes. A 0.5 M calcium chloride solution was added in four batches, and the stirring was continued for 60 minutes to obtain a gel solution;

[0057] S3: Add three-quarters of MCT medium-chain triglycerides and Tween-80 to a beaker, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, set the speed to 3000 rpm, and slowly add the gel solution prepared in step S2 under continuous stirring, emulsify for 20 minutes, and let it stand for 30 minutes after emulsification to obtain an emulsion;

[0058] S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel. Set the freeze dryer temperature to -50°C and the vacuum degree to 0.1 mbar. Dry the pre-frozen gel at -50°C for 24 hours, then heat it to 20°C at a rate of 1°C / min and dry it for 6 hours to obtain gel particles.

[0059] S5: Beeswax and one-quarter of the weight of MCT medium-chain triglycerides were mixed and heated in a water bath to 70°C for complete dissolution to obtain a coating solution. The gel particles prepared in step S3 were preheated to 40°C and then added to the coating solution. After stirring for 1.5 minutes, the gel particles were separated by a sieve and immediately cooled to 4°C for solidification to obtain a konjac hydrogel polymer.

[0060] Example 3: A highly absorbent konjac hydrogel polymer comprises the following raw materials in parts by weight: 35 parts of acetylated konjac glucomannan, 12 parts of modified chitosan, 6 parts of calcium chloride solution, 2 parts of acetic acid solution, 4 parts of nanocellulose, 3 parts of beeswax, 12 parts of MCT medium chain triglycerides and 2 parts of emulsifier.

[0061] Preparation of acetylated konjac glucomannan:

[0062] A1: Konjac glucomannan was added to distilled water and stirred to dissolve uniformly to obtain an 8 wt% Konjac glucomannan solution; 200 mL of the Konjac glucomannan solution was cooled to 4°C, and then sodium citrate was added to adjust the pH to 6.8. 3 mL of acetic anhydride was slowly added dropwise with continuous stirring, and the mixture was stirred for 2.5 hours. After the reaction was completed, ethanol was added to terminate the reaction, and the mixture was centrifuged at 6000 rpm for 10 minutes. The mixture was washed with distilled water until neutral, and then dried under vacuum at 55°C to constant weight to obtain acetylated Konjac glucomannan;

[0063] Preparation of modified chitosan:

[0064] B1: Dissolve chitosan in 0.1M acetic acid aqueous solution and stir to dissolve uniformly to obtain a chitosan solution with a concentration of 1.5wt%. Dissolve 100mg of hexadecyltrimethylammonium bromide in 500mL of dimethyl sulfoxide solvent, heat to 50°C in a water bath, and stir to dissolve uniformly to obtain a hexadecyltrimethylammonium bromide solution.

[0065] B2: Slowly add 400 mL of the hexadecyltrimethylammonium bromide solution prepared in step B1 dropwise to 500 mL of the chitosan solution, heat in a water bath to 55°C, control the pH to 4.5, react for 3 h, pour the reaction solution into 3000 mL of ethanol solution three times, centrifuge, filter, and wash with ethanol three times, and dry in a vacuum at 60°C to constant weight to obtain modified chitosan;

[0066] Preparation of konjac hydrogel polymer:

[0067] S1: dissolving acetylated konjac glucomannan in distilled water and stirring to dissolve uniformly to obtain a 2 wt% acetylated konjac glucomannan solution; dissolving modified chitosan in 0.15 M acetic acid solution and stirring to dissolve uniformly to obtain a chitosan solution; adding nanocellulose to distilled water and ultrasonically dispersing the mixture to obtain a 1.5 wt% nanocellulose suspension;

[0068] S2: Slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH to 6 during the process, stirring continuously for 50 minutes, then adding the nanocellulose suspension prepared in step S1 in three batches, stirring continuously for 40 minutes, and adding 0.4M calcium chloride solution in four batches, stirring continuously for 50 minutes to obtain a gel solution;

[0069] S3: Add three-quarters of MCT medium-chain triglycerides and glyceryl monostearate to a beaker, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, set the speed to 2800 rpm, and slowly add the gel solution prepared in step S2 under continuous stirring, emulsify for 15 minutes, and let it stand for 30 minutes after emulsification to obtain an emulsion;

[0070] S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel. Set the freeze dryer temperature to -50°C and the vacuum degree to 0.1 mbar. Dry the pre-frozen gel at -50°C for 24 hours, then heat it to 20°C at a rate of 1°C / min and dry it for 6 hours to obtain gel particles.

[0071] S5: Mix beeswax and one-quarter of the weight of MCT medium-chain triglycerides, heat in a water bath to 70°C to completely dissolve, and obtain a coating liquid. Preheat the gel particles prepared in step S3 to 40°C, then add them to the coating liquid. After stirring for 2 minutes, separate the gel particles with a sieve, and immediately cool at 4°C to solidify to obtain a konjac hydrogel polymer.

[0072] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that konjac glucomannan is used in place of acetylated konjac glucomannan in Comparative Example 1.

[0073] Comparative Example 2: The operation of Comparative Example 2 is basically the same as that of Example 2, except that chitosan is used instead of modified chitosan in Comparative Example 2.

[0074] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 2, except that nanocellulose is not used in Comparative Example 3.

[0075] Comparative Example 4: The operation of Comparative Example 4 is basically the same as that of Example 2, except that the interfacial induction method is not used in Comparative Example 4, and the gel solution is directly freeze-dried.

[0076] Performance testing:

[0077] Water absorption test: 1 g of the konjac hydrogel polymer prepared in Example 2 and Comparative Examples 1 to 4 was taken and placed in deionized water (control group), simulated gastric juice (0.2 w / v% NaCl solution and 0.7 w / v% HCl solution preparation, pH 1.2, 37 ° C) and simulated intestinal fluid (PBS buffer, pH 7.4, 37 ° C), with an oscillation rate of 100 rpm, simulating the dynamic environment in the human stomach. Samples were taken out and measured every 0.25 h, 0.5 h, 1 h, 2 h and 6 h. After recording the weight of the sample after water absorption, the sample was put back and continued to soak. Water absorption rate=(sample weight after water absorption-initial weight) / initial weight was calculated. The deionized water test result was as follows: Figure 1 As shown; simulated gastric fluid test as Figure 2 As shown; simulated intestinal fluid test as Figure 3 shown.

[0078] Depend on Figure 1 、 Figure 2 and Figure 3 The results show that the konjac hydrogel polymer prepared by the present invention has a low water absorption rate in the early stage, and the water absorption rate accelerates over time, effectively avoiding the discomfort reaction caused by excessive water absorption in the early stage, while ensuring effective acid resistance and high water absorption; Figure 1 As a result, comparative example 1 has a faster initial water absorption rate, which may be due to the fact that the konjac glucomannan that is not acetylated has a stronger hydrophilicity; comparative example 2 has a higher initial water absorption rate, especially in the 1h to 2h stage, which may be due to the fact that the acetylated konjac glucomannan has delayed the initial water absorption rate, but due to the strong hydrophilicity of unmodified chitosan, the water absorption rate is gradually improved in the middle and late stages; the initial water absorption rate of comparative example 3 is similar to that of Example 2, but its total water absorption capacity is significantly lower than that of Example 2, which may be due to the lack of high specific surface area and water absorption performance of nano cellulose, the water absorption speed is slower, the water absorption rate is lower, and the physical reinforcement effect of nano cellulose is missing, and the structural stability is poor; the water absorption rate of comparative example 4 is unstable, which may be due to the lack of uniform pore structure generated by the interface induction method, the water absorption path is limited, and the water absorption rate and capacity are significantly affected.

[0079] Depend on Figure 2As a result, comparative example 1 shows a lower water absorption rate in the early stage, and the water absorption rate is also significantly reduced. This may be due to the poor acid resistance of unacetylated konjac glucomannan in an acidic environment and easy degradation, resulting in damaged gel structure, gel degradation so that the water absorption rate is limited, and may cause gel fragmentation, and thus cause a significant decrease in water absorption capacity; comparative example 2 shows a lower water absorption rate in the early stage, and the water absorption rate is significantly reduced after 2h. This may be due to the fact that unmodified chitosan is easily soluble in an acidic environment, affecting the stability of the gel, and the gel structure is destroyed due to the dissolution of chitosan, and the water absorption capacity is reduced; comparative example 3 also shows an extremely low water absorption rate in the early stage, and the water absorption rate is significantly reduced. This may be due to its lack of nanocellulose structure instability, the mechanical strength and toughness of the hydrogel in the water absorption process are poor, and the overall structure is loose and causes; comparative example 4 absorbs water slowly in the early stage, and the water absorption rate is low, which may be due to the lack of pore structure generated by the interface induction method, and the structural stability is poor.

[0080] Depend on Figure 3 As a result, comparative example 1 shows a faster initial water absorption rate, but the water absorption rate in the later stage is significantly decreased. This may be due to the fact that the unacetylated konjac glucomannan is highly hydrophilic under a neutral environment and absorbs water quickly, but too fast water absorption can cause the gel to expand excessively, destroying the internal cross-linked network, causing structural damage and a decline in water absorption capacity; comparative example 2 also shows a faster initial water absorption rate and a higher water absorption rate, which may be due to the fact that the unmodified chitosan is highly hydrophilic and absorbs water quickly; comparative example 3 shows a lower initial water absorption rate, and the water absorption rate is also lower, which may be due to the lack of nanocellulose, insufficient mechanical strength and pore structure, which limits water penetration and limited water absorption rate; comparative example 4 shows a slow water absorption rate, but the water absorption rate is lower, which may be due to the lack of pore structure produced by the interface induction method, and the pore structure is not uniform enough, the water absorption path is limited, and the water absorption rate and capacity are affected.

[0081] Mechanical strength test: Use a universal material testing machine, set the compression mode, place the konjac hydrogel polymer samples prepared in Example 2 and Comparative Examples 1 to 3 in a compression fixture, gradually increase the pressure, and record the maximum compression force before the hydrogel breaks or deforms. The results are as follows: Figure 4 shown.

[0082] Depend on Figure 4As a result, the konjac hydrogel polymer prepared by the present invention has excellent mechanical strength; Comparative Example 1 shows poor mechanical strength, which may be due to the higher hydrophilicity of unmodified konjac glucomannan, lacking the structural stability brought by acetylation modification, and water molecules easily and quickly enter the gel interior, thereby causing the gel to be more easily deformed during compression; Comparative Example 2 shows poor mechanical strength, which may be due to the hydrophobic interaction and molecular arrangement tightness brought by the long-chain modification of chitosan can be missing, causing the gel network structure to show poor stability during compression; Comparative Example 3 shows extremely poor mechanical strength, which may be due to not using nano cellulose, greatly weakening the supporting structure of the hydrogel, lacking the physical reinforcement effect of nano cellulose, and the gel is more likely to break when compressed; Comparative Example 4 shows poor mechanical strength, which may be due to the synergistic effect of lacking the interfacial induction method, and the pore structure generated by the hydrogel after freeze drying is less and irregular, causing it to be more likely to break during compression.

[0083] Biocompatibility test: The konjac hydrogel polymer prepared in Examples 1 to 3 was placed in sterile PBS buffer and extracted at 37°C for 24 hours. The extract was collected and sterilized by filtration with a 0.22 μm filter membrane. Human intestinal epithelial cells (Caco-2 cells) were inoculated into 96-well plates, with 1×10 cells per well. 4 Cells were cultured in a 37°C, 5% CO2 incubator for 24 hours. The culture medium was discarded and 100 μL of hydrogel extract was added for 24 hours. After the culture period, 20 μL of MTT reagent (5 mg / mL) was added to each well and cultured for another 4 hours. The culture medium was aspirated and 150 μL of DMSO was added to dissolve the formazan crystals in the cells. The cells were shaken and mixed for 5 minutes. The absorbance was measured at 570 nm using a microplate reader. The cell survival rate was calculated as (absorbance of the experimental group - absorbance of the control group) × 100%. The control group was added with normal saline. The results are shown in Figure 2. Figure 5 shown.

[0084] Depend on Figure 5 The results show that the konjac hydrogel polymer prepared by the present invention has excellent biocompatibility, does not cause adverse effects on the human body, and can be effectively used in food and pharmaceutical preparations.

[0085] Spectrum test: The SEM spectrum of the konjac hydrogel polymer sample prepared in Example 2 was tested using a scanning electron microscope. The results are as follows: Figure 6 shown.

[0086] Depend on Figure 6The results show that the present invention successfully and effectively prepared a konjac hydrogel polymer, with an obvious porous structure and pore distribution in the image. A large number of evenly distributed pores are shown in the image, forming a three-dimensional network structure. This porous property is consistent with the expected structure of the highly absorbent hydrogel, and the pore wall structure is clear and thick, showing a supportive network, showing the result of the joint action of nanocellulose and cross-linking agent (calcium ions). The entire image presents a porous network with good continuity, and the pores are interconnected, which conforms to the structural characteristics that should be had after the interfacial induction method and freeze-drying treatment.

[0087] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A highly water-absorbent konjac hydrogel polymer, characterized in that The composition includes the following raw materials in parts by weight: 30-40 parts of acetylated konjac glucomannan, 10-15 parts of modified chitosan, 5-8 parts of calcium chloride solution, 1-3 parts of acetic acid solution, 3-5 parts of nanocellulose, 2-5 parts of beeswax, 10-15 parts of MCT medium chain triglyceride and 1-3 parts of emulsifier; The emulsifier is any one of lecithin, Tween-80 and glyceryl monostearate; The concentration of the calcium chloride solution is 0.2-0.5M; the concentration of the acetic acid solution is 0.1-0.2M; The specific preparation steps of the acetylated konjac glucomannan are as follows: A1: adding konjac glucomannan to distilled water, stirring and dissolving uniformly to obtain a konjac glucomannan solution; cooling the konjac glucomannan solution, then adding sodium citrate to adjust the pH, slowly adding acetic anhydride dropwise under continuous stirring, stirring for reaction, and after the reaction is completed, adding ethanol to terminate the reaction, centrifuging, washing with distilled water until neutral, and vacuum drying to constant weight to obtain acetylated konjac glucomannan; In step A1, the amount of acetic anhydride used is 1-2% of the volume of the konjac glucomannan solution; The specific preparation steps of the modified chitosan are as follows: B1: Dissolve chitosan in 0.1M acetic acid aqueous solution, stir and dissolve evenly to obtain a chitosan solution; dissolve hexadecyltrimethylammonium bromide in dimethyl sulfoxide solvent, heat in a water bath, stir and dissolve evenly to obtain a hexadecyltrimethylammonium bromide solution; B2: slowly drop the hexadecyltrimethylammonium bromide solution prepared in step B1 into the chitosan solution, heat in a water bath, control the pH, and after the reaction is completed, pour the reaction solution into an ethanol solution three times, centrifuge, filter, and wash with ethanol three times, and vacuum dry at 60°C to constant weight to obtain modified chitosan; In step B1, the ratio of the amount of hexadecyltrimethylammonium bromide to the dimethyl sulfoxide solution is 0.15-0.3 g:1 mL; In step B2, the volume ratio of the hexadecyltrimethylammonium bromide solution to the chitosan solution is 0.6 to 1:1; The specific preparation steps of the highly water-absorbent konjac hydrogel polymer are as follows: S1: dissolving acetylated konjac glucomannan in distilled water, stirring and dissolving uniformly to obtain an acetylated konjac glucomannan solution; dissolving modified chitosan in acetic acid solution, stirring and dissolving uniformly to obtain a chitosan solution; adding nanocellulose to distilled water, dispersing uniformly by ultrasonic treatment, and obtaining a nanocellulose suspension; S2: slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH during the process, stirring continuously, and after the reaction is completed, gradually adding the nanocellulose suspension prepared in step S1, stirring continuously, and after the reaction is completed, gradually adding the calcium chloride solution, stirring continuously, to obtain a gel solution; S3: Add three quarters of MCT medium chain triglyceride by weight to a beaker, add an emulsifier, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, and slowly add the gel solution prepared in step S2 under continuous stirring to emulsify the reaction, and let stand after the emulsification is completed to obtain an emulsion; S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel particles; S5: beeswax and one quarter of the weight of MCT medium chain triglyceride are mixed, and the mixture is completely dissolved by heating in a water bath to obtain a coating liquid, the gel particles prepared in step S3 are preheated, and then added to the coating liquid, and after stirring, the gel particles are separated by a sieve, and the mixture is immediately cooled and solidified to obtain a konjac hydrogel polymer; In step S2, the nanocellulose suspension is added in three batches; the calcium chloride solution is added in four batches; In step S4, the specific operation of the freeze-drying treatment is as follows: the temperature of the freeze dryer is set to -50°C and the vacuum degree is 0.1 mbar, the pre-frozen gel is dried at -50°C for 24 hours, and then the temperature is increased to 20°C at a rate of 1°C / min and dried for 6 hours.

Citation Information

Patent Citations

  • Method for preparing functional soluble and edible compound membranes

    CN105646951A

  • Preparation method for constructing composite hydrogel by compounding collagen base and nonionic polysaccharide

    CN106496608A